Superconducting quantum point contacts - Bretheau, L. (2012)
We review our experiments on the electronic transport properties of atomic contacts between metallic electrodes, in particular superconducting ones. Despite ignorance of the exact atomic configuration, these ultimate quantum point contacts can be manipulated and well characterized in-situ. They allow performing fundamental tests of the scattering theory of quantum transport. In particular, we discuss the case of the Josephson effect. Nous décrivons un ensemble d'expériences de transport électronique que notre groupe a réalisées sur des contacts atomiques entre des électrodes métalliques, en particulier dans l'état supraconducteur. Bien que leur configuration atomique exacte ne soit pas connue, ces contacts ponctuels quantiques peuvent être manipulés et caractérisés in-situ, et permettent de mener à bien des tests fondamentaux de la théorie en diffusion du transport quantique. Nous discutons en particulier le cas de l'effet Josephson.